1991
DOI: 10.1093/oxfordjournals.humrep.a137335
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid and ovarian function in infertile women

Abstract: The aim of this study was to examine more closely the interaction between thyroid function and pituitary--ovarian axis in infertile women. In 185 infertile women without clinical signs of thyroid dysfunction, TRH-tests (TSH basal and 30 min after 200 micrograms TRH i.v.) were performed in the early follicular phase in addition to routine hormonal checks (gonadotrophins, oestradiol, DHEAS, testosterone, prolactin). The women were classified as euthyroid (n = 74; TSH stim 5-20 mU/l), latent hyperthyroid (n = 31;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
2
7

Year Published

1992
1992
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(70 citation statements)
references
References 0 publications
3
58
2
7
Order By: Relevance
“…On the other hand, Gerhard et al suggested that secretion of TSH and prolactin, which are stimulated by thyrotropinreleasing hormone, was significantly higher in infertile patients than in healthy fertile women [4,5]. However, in this study, prolactin levels were almost within the normal range in infertile patients, primarily because TSH levels were in the normal range, and were less strongly correlated with AMH levels in single regression analysis (p=0.623).…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…On the other hand, Gerhard et al suggested that secretion of TSH and prolactin, which are stimulated by thyrotropinreleasing hormone, was significantly higher in infertile patients than in healthy fertile women [4,5]. However, in this study, prolactin levels were almost within the normal range in infertile patients, primarily because TSH levels were in the normal range, and were less strongly correlated with AMH levels in single regression analysis (p=0.623).…”
Section: Discussioncontrasting
confidence: 79%
“…The prevalence of subclinical hypothyroidism, characterized by aberrant high serum thyroid-stimulating hormone (TSH) levels with normal free thyroxine (FT4) levels, in infertile women is reported to be approximately 20 % and it is a primary cause of subfertility [2,3]. Indeed, average TSH levels in infertile women were reportedly higher than those in normal fertile women [4,5]. And elevated serum TSH levels were associatAlthough levothyroxine replacement therapy for subclinical hypothyroidism in infertile patients remains debatable, thyroxine supplementation may improve fertility, in particular, implantation and miscarriage rates, leading to successful pregnancy [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Abalovich et al have reported endometriosis was nearly 2 times more compared to control group (25% vs 14%) and Gerhard et al reported endometriosis was nearly 5 times more (44% vs 9%). 17,33 Similarly, in patients with polycystic ovarian disease ATA positivity was significantly higher compared to control group. 42,43 Even association of this antibody positivity with premature ovarian insufficiency was also suggested.…”
Section: Autoimmune Thyroid Diseasesmentioning
confidence: 80%
“…Thus, a clinical picture in close relationship with menstrual irregularity, infertility, miscarriage and complications of unwanted pregnancy may occur. 16,17 The prevalence in the population is approximately 2-4%. 18 Even though there are several rare causes of hypothyroidism as post-iode 131 treatment, post thyroiditis and drug induced hypothyroidism, the main reason of hypothyroidism is immunological.…”
Section: Hypothyroidismmentioning
confidence: 99%
“…14 In a study by Grassi et al on 129 women from couples with infertility, six women (4.6%) had hypothyroidism, and five of the six women i. e. 83.33% had TAI. 9 Negro et al studied 416 women who underwent assisted reproductive techniques of these 42 (10.1%) were TPO positive, and concluded that in euthyroid women undergoing ART the pregnancy and delivery rates are not affected by the presence of TPOAb.…”
Section: Correlation Of Thyroid Autoimmunity and Thyroid Dysfunctionmentioning
confidence: 97%